The Brazilian City and the Negation of the Other (Alternautas, 2014)
Historically, cities have not been equally friendly and accommodating to everybody. Indeed, they were born from the identification and consolidation of a group of “equals” who shared the aim of protecting their own interests and defending themselves from the encroachments of the “other”. In the classical Greek city examples of this were strangers and prisoners of war. In the medieval European city the sick, such as lepers, and the jobless were those branded “undesirable” (Le Goff 1997). Presently, Arabs and black Africans, in Western Europe, and Latino immigrants, in the United States, are some examples of those who are frequently considered the others. Despite the extensive contributions of the English-speaking scientific community to the understanding of these classification and differentiation processes (e.g. Jenkins 2000), scholars have overlooked the reproduction of this discrimination in the so-called “global south”. In this short article I will cover particular aspects of the Brazilian case and show how the negation of the other, here, is not limited to actions and discourse, but also materializes in urban forms dedicated to separating and rejecting undesirable persons.